Golgi Manganese Transport Is Required for Rapamycin Signaling in Saccharomyces cerevisiae - Devasahayam, Gina (Copyright © 2007 by the Genetics Society of America, 2007)
The Pmr1 Golgi Ca(2+)/Mn(2+) ATPase negatively regulates target of rapamycin complex (TORC1) signaling, the rapamycin-sensitive TOR complex in Saccharomyces cerevisiae. Since pmr1 causes resistance to rapamycin and tor1 causes hypersensitivity, we looked for genetic interactions of pmr1 with tor1. Deletion of TOR1 restored two wild-type phenotypes. Loss of TOR1 restored the ability of the pmr1 strain to grow on media containing 2 mm MnCl(2) and conferred wild type as well as the wild-type sensitivity to rapamycin. Mn(2+) additions to media partially suppressed rapamycin resistance of wild type and pmr1 tor1, suggesting that Tor1 and Tor2 are regulated by manganese. We parsed the roles of Ca(2+) and Mn(2+) transport and the compartments in rapamycin response using separation-of-function mutants available for Pmr1. A strain containing the D53A mutant (Mn(2+) transporting) of Pmr1 is rapamycin sensitive, but the Q783A mutant (Ca(2+) transporting) strain is rapamycin resistant. Mn(2+) transport into the Golgi lumen appears to be required for rapamycin sensitivity. Overexpression of Ca(2+) pump SERCA1, Ca(2+)/H(+) antiporter Vcx1, or a Mn(2+) transporting mutant of Vcx1 (Vcx1-M1) failed to restore rapamycin sensitivity, and loss of Pmr1 but not other transporters of Ca(2+) or Mn(2+) results in rapamycin resistance. Overexpression of Ccc1, a Fe(2+) and Mn(2+) transporter that has been localized to Golgi and the vacuole, does restore rapamycin sensitivity to pmr1Δ. We conclude that Mn(2+) in the Golgi inhibits TORC1 signaling.